History and human survival - Lifton, Robert Jay (Random House, 1970)
The fact that Robert Jay Lifton has written about the survivors of the atomic bombing of Hiroshima, the personality and psychological processes of revolution in China, and women and young people as contemporary forces in social history, is but testament to the relevance of his ideas to "radical historical moments like ours".